Kinerja Pegawai Dalam Meningkatkan Pelayanan Di Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kota Palangka Raya - Mita Sari; Dessy Kumalasari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Quality of performance is one of the problems that is not far from the service. For the Service society is the thing that happens and is obtained almost every day. Good service greatly affects the quality of performance of an employee in an organization. As we know the performance of employees at the Office of Investment and integrated service one door of the city of Palangkaraya still less because of its employees lack of human resources so in terms of service is not maximized. The purpose of this research is to know how employees are performing in improving the office of Investment and Integrated services at one door of Palangkaraya city. The research method used is qualitative, this study uses the theory of Fuad Mas'ud which contains quality, quantity, timeliness, effectiveness, and kemitmen work. The data collection techniques in this study are observations, interviews, documentation. The results of the research can be concluded that the performance of employees in improving the service at DPM-PTSP Palangkaraya city is still not optimal, seen from five indicators namely quality, quantity, timeliness, effectiveness, and work commitments. Obstacle factors that can mengahmbat the way of service, among others, human resources or employees who are less particularly in the field of service that is evidenced by employees lacking control of the field of service and the delay of time given in carrying out its duties are not appropriate. In addition to the inhibitory factor there are also supporting factors that are encouraging and mutually encouraging each other and carrying out their duties to share because the ability of human resources can help each other in carrying out their duties and to cover the lack of unfinished work and try to provide the best service.